Pengaruh Kesadaran Merek, Kualitas Produk, Dan Kepercayaan Merek Terhadap Pembelian Ulang (Studi Kasus pada Konsumen Wardah Di Store Bravo Tulungagung) - Harini, Restu Widya; Salim, Muhammad Agus; Slamet, Afi Rachmat (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to determine the influence of brand awareness, product quality and brand trust on repurchase (case study on Wardah consumers at Bravo Tulungagung Store). In this study, the number of the population is unknown. Therefore, this study uses the Lemeshow formula to determine the number of samples, with a result of 100 respondents. This study uses primary and secondary data sources as well as data collection methods using online questionnaires (Google From). For data analysis, SPSS Version 25 software was used to analyze instrument tests, classical assumption tests, multiple linear regression tests, hypothesis tests, and determination coefficient tests. The results of this study show that the variables of brand awareness, product quality and brand trust have a simultaneous effect on the repurchase of Wardah products at the Bravo Tulungagung Store. The brand awareness variable had a significant effect on the repurchase of Wardah products at the Bravo Tulungagung Store. Product quality variables have a significant effect on the repurchase of Wardah products at the Bravo Tulungagung Store. However, the brand trust variable did not have a significant influence on the repurchase of Wardah products at the Bravo Tulungagung Store. Keywords: Brand Awareness, Product Quality, Brand Trust, Repurchase